Legal Standing Influencer Saham di Indonesia - Pahlevi, Farida Sekti (Institut Agama Islam Negeri Ponorogo, 2021)
Investment is one of the factors driving economic growth in realizing economic equality and eradicating poverty. Economic Activities Investment plays a role in the development of companies or projects with the aim of obtaining profit sharing. The investment currently discussed in this study is a stock investment in the capital market. The growth of investors in the Indonesian capital market is considered quite good but is still relatively lagging behind other countries. One strategy to increase economic activity in the capital market sector is to utilize stock influencers. This study uses a literature study technique in collecting data in which the authors collect information related to legal reviews of the role of stock influencers in Indonesia. The formulation of the problem in this study focuses on (1) the influence of stock influencers on the number of investors, (2) prohibitions in the capital market industry, and (3) the role of stock influencers in terms of the Capital Market Law. The conclusion explains that stock Influencers provide information about stock investment well so that it can increase the number of investors, but requires a persuasive and educational approach to Influencers in order to know the risks and impacts as a whole and how to educate the public to invest properly. Then explained that the prohibition on the capital market and the role of stock influencers according to the Capital Market Law have not been explicitly regulated so it must be noted that influencers are not investment advisors and cannot be investment advisors, Influencers are not capital market supporting profession, Information submitted by influencers must heed Article 79 of the Capital Market Law, Influencer behaviour is viewed from actions that are prohibited in the capital market sector according to the provisions of articles 90-96 of the Capital Market Law.